RELATIONSHIP OF PHYTOPLANKTON ABUNDANCE WITH PRIMARY PRODUCTIVITY LEVEL IN BEACH WATERS KECAMATAN DUMAI BARAT PROVINSI - Irvina Nurrachmi; Waidia Dipeta Ym (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This research was conducted in May 2017 located on the coast of West Dumai Subdistrict, Riau Province. This Study aims to determine the relationship between the abundance of phytoplankton and the level of primary productivity in coastal waters of Dumai Barat District, Riau Province. The method used during this research is a survey method and the determination of station points by purposive sampling. Sampling of water quality parameters in situ. The results of the calculation of phytoplankton abundance ranged from 6,200 mg/l and phytoplankton species were found the most from the Bacillariophyceae class of 14 species. Simple linear regression test results of the relationship of abundance of phytoplankton with primary productivity at each station are shown by the mathematical equation Y 1.2911x + 2.8 with the coefficient of determination (R2) 0.1839. It can be concluded that the higher the abundance of phytoplankton, the higher the level of primary productivity.